Assistants of the ulus trustee: legal status and career preferences - I. V. Lidzhieva (Nomadic Civilization: Historical Research, 2023)
The subject of the study of this article is the corps of assistant ulus trustees – mid-level officials of the management system of the Kalmyk steppe – in the period from 1867 to 1917 through the prism of the prosopographic approach, i.e. by analyzing their career strategies. The basis of the source base was made up of formal lists about the service of officials, as well as clerical documentation of the central and ulus departments, identified in the funds of a number of regional archives of the Russian Federation. Despite the lack of clear legal norms in imperial legislation defining the functional responsibilities of assistants, as well as constant travel across the steppe, the vastness of the territory, and the lack of familiar infrastructure, there were many who wanted to devote themselves to service in the management of small nationalities. But not everyone was delayed for long due to planned further advancement beyond the Kalmyk steppe or as a result of noncompliance with unspoken job requirements. This trend explains the frequent turnover of personnel and their shortage. In the course of the study, the author, having determined the average length of service of assistant trustees in ulus departments, focuses on their social origin and states the presence of nepotism. The corps of assistants represented social capital formed during the 19th and early 20th centuries. from representatives of different estates. As a result of the study, the hypothesis put forward about the interdependence of class and nepotism is confirmed by a number of facts that clearly illustrate it. While settling down themselves, officials sought to help their relatives, providing them with protection and further ensuring their career advancement.